The Level of Interest Regarding Nutrition Issues Among the Selected Group of Children and Teenagers Aged 10–16 Years - Platta, A.; Pukszta, T. (Scientific Journal of Gdynia Maritime University, 2018)
The main aim of the study was to assess the level of interest regarding nutrition issues among the selected group of children and adolescents aged 10–16 years. The study was conducted in a group of 260 children, including 130 elementary school pupils (66 girls and 64 boys) and 130 junior high school students (68 girls and 62 boys) aged from 10 to 16 years. Each respondent had to determine his/her attitude to the statements made in the study according to the 5-point Likert scale with boundary marks "definitely not" (1) to "definitely yes" (5). The final conclusion based on the conducted studies was that the level of interest regarding nutrition issues among the selected group of children was indifferent.